Inovasi Pengembangan Sistem Informasi Pengelolaan Surat Keterangan Pendamping Ijazah Berbasis Web - Tito Sugiharto; Mohammad Irwansyah (STMIK Budi Darma, 2020)
This research was aiming to produce a management information system for Diploma Companion Certificate (SKPI). The target of the research to be achieved is the existence of an information system that can be used to manage the filling and printing of Companion Certificates. Management information system This Certificate of Companion is made to be applied in the Informatics Engineering Study Program S1 Faculty of Computer Science, University of Kuningan. This study discusses how the process of designing and developing an information system for managing Diploma Certificates of Completion in the S1 Informatics Engineering Study Program. The absence of an application or information system for managing Diploma Certificates is a serious problem that must be considered. Managers of the S1 Informatics Engineering Study Program find it difficult in the process of making and filling Diploma Companion Certificates for their graduates. In the absence of a management information system, a Diploma of Companion Certificate, the process of making and filling with Certificate ofCompanion Certificate will take a long time. The method used in this study is Rational Unified Process (RUP). There are four stages in the use of this RUP method, namely the stages of inception, elaboration, construction and transition. The design model used in this study uses Unified Modeling Language (UML). The testing process is carried out using the Black Box Testing. Therefore, to solve these problems, an innovation is needed In the management ofa web-based Diploma Companion Certificate. It is expected that this information system can help and ease the Study Program in managing Diploma Companion Certificates.